Impacts of Bradyrhizobium inoculants on growth and yield of tropical soybean (Glycine max (L.) Merr.) cultivars, soil health and soil microbiome - Akley, KorblaEdwin (Kansas State University, 2019)
Microbial inoculation of grain legumes improves crop yield and soil quality. Grain legumes such as soybean as requires host specific Brayrhizobium japonicum to enhance growth, nitrogen fixation, and grain yield. However, limited information exists on how commercial Bradyrhizobium inoculants affect symbiotic plant performance and yield of soybean, and as well as soil health in Ghana’s cropping systems. A field study (2-yr) was conducted at CSIR-Savanna Agricultural Research Institute’s experimental field at Nyankpala, Ghana to determine the impacts of Bradyrhizobium inoculants on; (1) growth, nodulation, nitrogen fixation, grain yield of soybean, and (2) soil biological and chemical properties. We also evaluated the commercial inoculants effects on the subsequent maize and soybean crops. The experiment was laid out as a split-plot design where the main plot consisted of tropical soybean (Glycine max crosses (TGX)) varieties; Jenguma (TGX1448-2E), Afayak (TGX1834-5E), and Songda (TGX 1445-3E). The subplot consisted of three commercial Bradyrhizobium japonicum inoculants with different strains, Biofix (USDA 110), NoduMax (USDA 110) and Legumefix (USDA 532c) plus an uninoculated control. Assessment was made on nodulation pattern, shoot biomass, nitrogen fixation, grain yield, and residual N balance. Bulk and rhizosphere soils were sampled and analyzed for soil pH, available soil N (NO3-N and NH4+-N) and P, and soil microbial community structure by phospholipids fatty acid (PLFA) analysis. Inoculants improved nodulation, shoot biomass, nitrogen fixation and grain yield of soybean. Greater responses were associated with NoduMax and Biofix. Inoculation increased grain yield by ~30 %. Commercial inoculants also increased microbial biomass, and available P and NH4+-N. Afayak outperformed the other soybean varieties for biomass dry matter, nodulation (nodule number) and grain yield. Afayak also stimulated greater microbial biomass and available P compared to Jenguma. Furthermore, enhance microbial biomass was found in the rhizosphere compared to the bulk soil due to soil enrichment with root exudate and commercial inoculants. In assessing, the previous year commercial inoculants effect on the subsequent soybean and maize crops, three (3) independent mineral N fertilizer rates (0, 50 and 100 kg N ha-1) were added to the soybean-maize rotation phase. Biofix yielded superior maize shoot dry matter and grain yield. Maize grain yield from previous commercial inoculants was equivalent to grain yield from 50 kg N ha-1mineral N fertilizer ). Thus inoculating soybean with commercial inoculants reduced mineral N nutrition for the subsequent maize crop by 50%. In the soybean-soybean phase, the previous Biofix and the uninoculated control produced significant soybean grain yield than the previous NoduMax. In conclusion, TGX soybean varieties exhibited superior performance when inoculated with commercial inoculants especially Biofix and NoduMax. However yearly inoculation of soybean is needed to sustain enhanced grain yield and soil quality in Northern Ghana.
Keywords: Agronomy; Soil Health; Soil Microbiome; Bradyrhizobium Inoculants; Tropical Soybean Cultivars; Grain Legumes-Cereal Rotation Systems